Inception report on Australian funded microfinance project for tbe north western region of Bangladesh - BRAC (© BRAC, 2016)
1. BRAC micro finance programme 2. Northwest region of Bangladesh 3. Project goal and objective 4. Project areas 5. Target beneficiaries 5. Description of key components 6. Project credit delivery model 7. Present MIS of micro finance Programme 8. Australian Identity